Calibration of crushable foam plasticity models for synthetic bone material for use in finite element analysis of acetabular cup deformation and primary stability. Issue 1 (2nd January 2019) - Schulze, Christian; Vogel, Danny; Sander, Manuela; Bader, Rainer
Abstract: Polyurethane (PU) foam is a material often used in biomechanical experiments and demands for the definition of crushable foam plasticity (CFP) in numerical simulations of the primary stability and deformation of implants, to describe the crushing behaviour appropriately. Material data of PU foams with five different densities (10–40 pounds per cubic foot were ascertained experimentally in uniaxial compression test and used to calibrate CFP models for finite element modelling. Additionally, experimental and numerical deformation, push-out and lever-out tests of press-fit acetabular cups were carried out to assess the influence of the chosen material definition (linear elastic and CFP) on the numerical results. Comparison of the experimentally and numerically determined force–displacement curves of the uniaxial compression test showed a mean deviation of less than 3%. In primary stability testing, the deviation between the experimental and numerical results was in a range of 0%–27% for CFP modelling and 64%–341% for the linear elastic model. The material definition selected, highly influenced the numerical results in the current study. The use of a CFP model is recommended for further numerical simulations, when a deformation of the foam beyond the yield strength is likely to occur.